The Monument as a Conceptual Archive of Political Discourse: A Philosophical Analysis from the Conceptual History - Cristiá, Felix Alejandro (2025)
This article analyzes the monument as a conceptual archive that tries to establish the permanence of political discourse on space, which in turn becomes the object that allows us to follow the change of meaning of the concepts that compose it. The study is approached mainly from conceptual history (Begriffsgeschichte), insofar as it focuses on the uses of concepts both at a given moment and according to their meaning changes throughout history. This can be useful to know the monument’s social scope –and legitimacy– as the container of collective memory. The memory the monument tries to make last can support the eventual update or delegitimization of the discourses that have conceptually erected it. Therefore, the monument itself can host its revocation.